Food Sharing Initiatives and Food Democracy: Practice and Policy in Three European Cities - Davies, Anna R. (2019)
Calls for greater food democracy in Europe have emerged as the limitations of urban food systems dominated by commercial organisations are documented, but little attention has been paid to how policy arrangements affect attempts to transition to more democratic food futures. This article examines food sharing initiatives—increasingly facilitated by the use of information and communication technologies—as a potential means to enhance urban food democracy, and explores the role of policy in shaping those practices in three European capital cities: Berlin, London, and Dublin. We pose two related questions: To what extent are diverse food sharing initiatives exemplars of food democracy, and to what extent do policy arrangements affect food sharing practices and the nature of any food democracy they might embody? Our empirical evidence demonstrates where the goals and impacts of food sharing initiatives align with key dimensions of food democracy. We also consider how food sharing initiatives—and any food democracy dimensions that they support—are affected by the policy environment in which they operate. The food sharing initiatives examined revealed to be agents of pro-democratic change, at least within the boundaries of their spheres of influence, despite policies rarely having their activities and aspirations in mind.